Direct and indirect single electron transfer (SET)-photochemical approaches for the preparation of novel phthalimide and naphthalimide-based lariat-type crown ethers - Cho, Dae Won; Mariano, Patrick S.; Yoon, Ung Chan (Beilstein Journal of Organic Chemistry, 2014)
In this review, we describe direct and indirect photochemical approaches that have been developed for the preparation of phthalimide- and naphthalimide-based, lariat-type crown ethers. The direct route utilizes a strategy in which nitrogen-linked side chains containing polyethoxy-tethered phthalimides and naphthalimides, possessing terminal α-trialkylsilyl groups, are synthesized utilizing concise routes and UV-irradiation to form macrocyclic ring systems. In contrast, the indirect route developed for the synthesis of lariat-type crown ethers employs sequences in which SET-promoted macrocyclization reactions of α-trialkylsilyl-terminated, polyethoxy-tethered phthalimides and naphthalimides are followed by a side chain introduction through substitution reactions at the amidol centers in the macrocyclic ethers. The combined observations made in these investigations demonstrate the unique features of SET-promoted photocyclization reactions that make them well-suited for the use in the synthesis of functionalized crown ethers. In addition, while some limitations exist for the general use of SET-photochemical reactions in large-scale organic synthesis, important characteristics of the photoinduced macrocyclization reactions make them applicable to unique situations in which high temporal and spatial control is required.
Keywords: lariat-type crown ethers; SET-promoted photocyclization; α-silylether-terminated imides